Parental Perceptions and Behaviors Regarding Child Weight Status among Toddlers Born Preterm - Saleska, Jessica Londeree; Sheppard, Kelly; Turner, Abigail Norris; Boone, Kelly M.; Keim, Sarah A. (American Journal of Perinatology, 2020)
Objective Childhood obesity is a significant determinant of adult obesity. Among children born preterm, rapid “catch-up growth” in infancy increases the risk of later obesity. Parental perceptions of their child's weight status may compound the child's biologically heightened risk of obesity.Study Design We performed a secondary analysis of data on parental perceptions of child weight status from a randomized controlled trial (2012–2017, n = 331 toddlers born preterm). We used the Child Feeding Questionnaire (CFQ) to measure parental child feeding behaviors and beliefs. We calculated the prevalence of incorrect weight estimation, and used t-tests and chi-square tests to compare sample characteristics by correct versus incorrect weight estimation. We calculated odds ratios (ORs) for factors associated with parental underestimation of child weight status.Results Most (90%) children were of normal weight, whereas 3% were underweight and 7% were overweight. A majority (75%) of parents correctly estimated their child's weight status. Incorrect weight estimation was only associated with child's actual weight. Parents of overweight children were more likely to underestimate their child's weight status than parents of normal weight children (OR: 2.23, 95% confidence interval: 2.00–2.49). Mean CFQ scores differed by the child's actual weight status but not by the child's estimated weight status.Conclusion Among these toddlers born preterm, significantly higher proportions of parents with underweight and overweight children incorrectly estimated their child's weight status relative to parents of normal weight children. Our findings suggest that weight underestimation could be a problem in this population, although it was not associated with changes in feeding practices.
Keywords: preterm; parental perception; obesity; weight; feeding practices